INHABITANT-ORIENTED ENVIRONMENTAL PREFERENCES AND LAYOUT STUDY OF SLAB HOUSE CLUSTERS IN "YANGTZE RIVER DELTA" AREA OF CHINA WITH MAS - X. Y. Ding (Lowland Technology International, 2013)
This paper has presented a design method of local inhabitant-oriented layout of slab house cluster including two main task: 1) analyzing inhabitants' preferences on environmental conditions in "Yangtze River Delta" Area in China through a household investigation; 2) simulating layout evaluated by the inhabitants' preferences. The investigation results showed: the local inhabitants have their own characteristics on environmental conditions, such as general preferences on layouts with dwelling units, roads, green land and individual preferences related with ages, sex, occupation etc. The simulation results showed the local design criterions, such as the most suitable height of house, the green land size and the conjunction way between dwelling units and their relations with the types of houses.